Nonsteroidal antagonists of the mineralocorticoid receptor. Issue 5 (September 2015) - Kolkhof, Peter; Nowack, Christina; Eitner, Frank
Abstract : Purpose of review: The broad clinical use of steroidal mineralocorticoid receptor antagonists (MRAs) is limited by the potential risk of inducing hyperkalemia when given on top of renin–angiotensin system blockade. Drug discovery campaigns have been launched aiming for the identification of nonsteroidal MRAs with an improved safety profile. This review analyses the evidence for the potential of improved safety profiles of nonsteroidal MRAs and the current landscape of clinical trials with nonsteroidal MRAs. Recent findings: At least three novel nonsteroidal MRAs have reportedly demonstrated an improved therapeutic index (i.e. less risk for hyperkalemia) in comparison to steroidal antagonists in preclinical models. Five pharmaceutical companies have nonsteroidal MRAs in clinical development with a clear focus on the treatment of chronic kidney diseases. No clinical data have been published so far for MT-3995 (Mitsubishi), SC-3150 (Daiichi-Sankyo), LY2623091 (Eli Lilly) and PF-03882845 (Pfizer). In contrast, data from two clinical phase II trials are available for finerenone (Bayer) which demonstrated safety and efficacy in patients with heart failure and additional chronic kidney diseases, and significantly reduced albuminuria in patients with diabetic nephropathy. Neither hyperkalemia nor reductions in kidney function were limiting factors to its use. Summary: Novel, nonsteroidal MRAs are currently tested in clinical trials. Based on preclinical and first clinical data, these nonsteroidal MRAs might overcome the limitations of today's steroidal antagonists.